Entrepreneurial intention among Rhodes University undergraduate students - Bell, Jonathan Andrew (Rhodes University, Faculty of Humanities, Department of Psychology, 2015)
The entrepreneurial intentions of university students are important factors to consider when developing entrepreneurship offerings at tertiary level institutions. This research study reports on pertinent findings from a study which set out to determine Rhodes university undergraduate students"Ÿ entrepreneurial intentions and their pull and push factors that have brought them to the decision to become entrepreneurs. A survey, using a 43 question structured web-based instrument was used to capture the responses from undergraduate students across different departments at Rhodes University, Grahamstown. Key findings suggest that few undergraduate students intend to enter into an entrepreneurship career immediately after completion of their studies, whereas many of the respondents were more interested in doing so five years after graduation. The vast majority of students were satisfied without having formal entrepreneurial education and factors such as previous employment in entrepreneurial activities, and family influence had a statistical significant relationship with entrepreneurial intention.
Keywords: Rhodes University -- Undergraduates; Entrepreneurship -- South Africa -- Grahamstown; Social cognitive theory; Intention; Attitude (Psychology); Influence (Psychology); South Africa -- Economic conditions -- 1991-